2020
DOI: 10.1002/app.49101
|View full text |Cite
|
Sign up to set email alerts
|

Compounding and characterization of recycled multilayer plastic films

Abstract: Mechanical recycling of multilayer plastic films from food packages was investigated. The multilayer films were manually separated from municipal solid waste, washed, grinded, and finally compounded at 0–100 wt% concentrations with virgin low‐density polyethylene (PE‐LD). Polyethylene grafted with maleic anhydride (PE‐g‐MA) compatibilizer was used in two of the compounds to replace 2 and 5 wt% of the PE‐LD to study its effect as well. PE‐g‐MA is expected to improve the mechanical properties of the compounds by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…In fact, it may happen that it is possible to valorize a recycled material only for an application other than the original one. It might be the case of a post-consumer packaging Polymers 2021, 13, 71 2 of 18 material, that after the recycling process cannot generally be re-used in a food-contact application (due to contaminants' migration issues), or because the resulting recycled material has composition and properties completely different compared with the virgin resin (for example, the mechanical recycling of multilayer films, made of different polymers types, results in polymer blends [11,12]).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it may happen that it is possible to valorize a recycled material only for an application other than the original one. It might be the case of a post-consumer packaging Polymers 2021, 13, 71 2 of 18 material, that after the recycling process cannot generally be re-used in a food-contact application (due to contaminants' migration issues), or because the resulting recycled material has composition and properties completely different compared with the virgin resin (for example, the mechanical recycling of multilayer films, made of different polymers types, results in polymer blends [11,12]).…”
Section: Introductionmentioning
confidence: 99%
“…These data highlight that, even for the pristine recycled materials, the G’ slope deviates from the power-law dependence of two expected for a monodisperse entangled linear polymer melt in the terminal region, and it progressively becomes lower by adding the nanofiller, the compatibilizer and both of them. While the values of G’ slope for the neat Fil-s, lots can be related to a quite large polydispersity index, which is expected in the case of recycled materials [ 26 , 27 ], the further reduced slope, particularly for the compatibilized nanocomposite systems based on Fil-s A, can be attributed to the formation of supramolecular structures, due to non-covalent silicate–silicate, polymer–polymer and/or silicate–polymer interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The results of mechanical testing for the fibre durability showed that PE fibres with and without rosin are durable and strong even when relatively large rosin concentration (10 w-%) is used during the polymer blending. The significant effect of the spinning temperature on the long-term thermal ageing (60 °C) emphasized the essence of processing-related parameters and induced phenomena, such as crystallinity [ 40 , 41 ] and for some events cross-linking [ 42 ], when using natural components, like rosin. The processing parameters are typically adjusted per specific application and design criteria of the polyfilament.…”
Section: Discussionmentioning
confidence: 99%